The creation of extra storage capacity in nitrogen-doped porous carbon as high-stable potassium-ion battery anodes. (30th June 2021) - Xu, Shikai; Cai, Le; Niu, Ping; Li, Zhiqiang; Wei, Lingzhi; Yao, Ge; Wang, Changlai; Zheng, Fangcai; Chen, Qianwang
Abstract: Porous carbonaceous materials have been extensively explored as promising anodes for potassium-ion batteries (KIBs), and their potassium storage capacities are always higher than the theoretical specific capacity (279 mA h g −1 ). However, the mechanism behind the extra capacity for KIBs in porous carbonaceous materials is rarely explored. Herein, we synthesized porous carbonaceous materials with interconnected nanopores modified by abundant edge-doped N atoms to investigate the mechanism for potassium-storage performance. The resulting NPCs-600 displays outstanding electrochemical performances with a high reversible capacity (409 mA h g −1 at 0.1 A g −1 after 200 cycles), excellent rate capability (235 mA h g −1 at 5 A g −1 ), and remarkable long-term cycling stability (167 mA h g −1 at 5 A g −1 after 10, 000 cycles). The remarkable performance results from the nanopores grafted by edge-doped nitrogen atoms on the inner surface which can adsorb more K + to enhance the capacity of carbon materials beyond K + intercalation mechanism. Furthermore, the density functional theory (DFT) calculations further demonstrate that nitrogen atoms doped on the edge of defects facilitate to the sorption of K +, providing the extra capacity for KIBs. Graphical abstract: The remarkable potassium storage performance of NPCs-600 results from the nanopores grafted by edge-doped nitrogen atoms on the inner surface which can adsorb more K+ to enhance the capacity of carbon materials, providing the extra capacity for KIBs. Image 1